Сільськогосподарська кооперація: проблеми, шляхи розв’язання - Мосіюк, Ігор Пилипович; Кудінова, Ірина Петрівна (My University, 2010)
Розглядаються основні проблеми утворення сільськогосподарських кооперативів. Наводиться характеристика послуг сервісних кооперативів в залежності від форми їх організації. Agrarian economic sector cooperation relation formation blocking main problems are considered. Agricultural service cooperatives non profit activity character substantiation dependably on juridical status of their founders is conducted.
Keywords: кафедра економічної теорії; сільськогосподарський кооператив; послуга; кооперація; agricultural cooperation; service; cooperation